Empirical measurement of pressure in negative pressure wound therapy for infected wounds: How long can it really stay under pressure?. Issue 2 (27th December 2018) - Cozza, Valerio; Pascale, Marco M.; Pepe, Gilda; Panzera, Rocco; Magalini, Sabina; Gui, Daniele
ABSTRACT: Surgical site infections represent one of the most common surgical complications. Negative pressure wound therapy is considered an effective wound management system, based on the principle that a negative pressure inside the wound can suction fluids and approximate wound edges. With the negative pressure wound therapy systems commercially available it is assumed that the pressure inside the wound is stable at the set values. We conducted a prospective experimental study to investigate this. The negative pressure level achieved inside the dressing was investigated at a standard distance from the pad of suction and at specific times in patients with surgical site infections. Pressure measurements were performed in 28 dressings in 14 patients admitted to the Emergency Surgery Department between April 2016 and June 2017. In general, the machine was set at a pressure of −100 mmHg. Negative pressure was measured with a portable pressure reader in the dressing sponge at a distance of 0, 1.5, and 3 cm from the suction pad at the time of dressing change at 24 and 48 hours. The data suggest that there is a significant decrease in negative pressure at both 1.5 and 3 cm from the suction pad at 48 hours from the dressing change ( p = 0.0001 and p < 0.0001, respectively). This preliminary study shows with statistical significance that the pressure inside the sponge of a negative pressure wound therapy system decreases after 48 hours, confirming that the pressure inside the system is not the same as the pressure reported by the machine and, instead of being stable, changes overtime.